Effect of cilostazol on in vitro production of sheep - Silva, Jossimara de Melo (2023)
The objective of this study was to evaluate the effect of including cilostazol in the in vitro maturation medium of oocytes on the in vitro production of sheep embryos. Oocytes were collected from ovaries obtained from a slaughterhouse by follicular aspiration with a vacuum pump. The oocytes were divided into four maturation groups: the CON group, where the cumulus-oocyte complexes were immersed in TCM-199 supplemented with 500 IU of penicillin, 0.5 mg of streptomycin, 1.25 µg of amphotericin, 0.2 mM of sodium pyruvate, 10% (v/v) fetal bovine serum (FBS), 10 ng/mL of epidermal growth factor (EGF), 10 µg/mL of FSH, 10 µg/mL of LH, 10 µg/mL of estradiol, and 100 µM of cysteamine; and in the CILO0.3, CILO1, and CILO10 groups, the oocytes were matured in the CON group medium without the addition of cysteamine and supplemented with concentrations of 0.3, 1, and 10 µM of cilostazol, respectively. After 24 hours, the oocytes were evaluated for the presence or absence of cumulus cells and the degree of expansion and then subjected to in vitro fertilization (IVF) with sperm in FIV medium. After IVF, the presumptive zygotes were cultured in vitro. Cleavage was evaluated on day 2, with day 0 being the start of IVF. Results were expressed as a percentage, and variables such as cumulus cell expansion and the number of cleaved structures were compared using the chi-square test in the Epi Info software (Epi Info 7.2.5, Atlanta, GA, USA, 2021). Results were considered significant when P < 0.05. All groups showed 100% cumulus cell expansion, and there were no significant differences in cumulus cell expansion degree between the cilostazol- and cysteamine-supplemented groups (P > 0.05), as well as no significant differences in cleavage rates between the cilostazol- and cysteamine-supplemented groups (P > 0.05).